Alkaloids from single skins of the Argentinian toad Melanophryniscus rubriventris (ANURA, BUFONIDAE): An unexpected variability in alkaloid profiles and a profusion of new structures - Garraffo, H. Martin (2012)
GC-MS analysis of single-skins of ten Melanophryniscus rubriventris toads (five collections of two toads each) captured during their breeding season in NW Argentina has revealed a total of 127 alkaloids of which 56 had not been previously detected in any frog or toad. Included among these new alkaloids are 23 new diastereomers of previously reported alkaloids. What is particularly distinguishing about the alkaloid profiles of these ten collections is the occurrence of many of the alkaloids, whether known or new to us, in only one of the ten skins sampled, despite two skins being obtained from each breeding site of the five populations. Many of the alkaloids are of classes known to have structures with branched-chains (e.g. pumiliotoxins and tricyclic structures) that are considered to derive from dietary mites. A large number of previously reported and new alkaloids are also of unclassified structures. Only a very few 3,5-disubstituted-indolizidine or -pyrrolizidine alkaloids are observed that have a straight-chain carbon skeleton and are likely derived from ant prey. The possible relationship of these collections made during the toad’s brief breeding episodes to sequestration of dietary arthropods and individual alkaloid profiles is discussed.